Accuracy of Immunodiagnostic Tests for Active Tuberculosis Using Single and Combined Results: A Multicenter TBNET-Study - Goletti, Delia; Stefania, Carrara; Butera, Ornella; Amicosante, Massimo; Ernst, Martin; Sauzullo, Ilaria; Vullo, Vincenzo; Cirillo, Daniela; Borroni, Emanuele; Markova, Roumiana; Drenska, Roumiana; Dominguez, José; et al. (PloS one, 2008)
The clinical application of IFN-gamma release assays (IGRAs) has recently improved the diagnosis of latent tuberculosis infection. In a multicenter study of the Tuberculosis Network European Trialsgroup (TBNET) we aimed to ascertain in routine clinical practice the accuracy of a novel assay using selected peptides encoded in the mycobacterial genomic region of difference (RD) 1 for the diagnosis of active tuberculosis in comparison with tuberculin skin test (TST), QuantiFERON-TB GOLD In-Tube (Cellestis Ltd., Carnegie, Australia) and T-SPOT.TB (Oxfordimmunotec, Abingdon, UK). 425 individuals from 6 different European centres were prospectively enrolled. We found that sensitivity of the novel test, TST, QuantiFERON-TB GOLD In-Tube and T-SPOT.TB was respectively 73.1%, 85.3%, 78.1%, and 85.2%; specificity was respectively 70.6%, 48.0%, 61.9% and 44.3%; positive likelihood ratios were respectively 2.48, 1.64, 2.05, and 1.53; negative likelihood ratios were respectively 0.38, 0.31, 0.35, 0.33. Sensitivity of TST combined with the novel test, QuantiFERON-TB GOLD In-Tube and T-SPOT.TB increased up to 92.4%, 97.7% and 97.1%, respectively. The likelihood ratios of combined negative results of TST with, respectively, the novel test, QuantiFERON-TB GOLD In-Tube and T-SPOT.TB were 0.19, 0.07 and 0.10. The assay based on RD1 selected peptides has similar accuracy for active tuberculosis compared with TST and commercial IGRAs. Then, independently of the spectrum of antigens used in the assays to elicit mycobacterial specific immune responses, the novel test, IGRAs, and the TST do not allow an accurate identification of active tuberculosis in clinical practice. However, the combined use of the novel assay or commercial IGRAs with TST may allow exclusion of tuberculosis.